Valuation of Commodity Futures and Options Under Stochastic Convenience Yields, Interest Rates, and Jump Diffusions in the Spot - Hilliard, Jimmy E.; Reis, Jorge (Journal of Financial and Quantitative Analysis, 1998)
Jimmy E. Hilliard, Jorge Reis, Valuation of Commodity Futures and Options Under Stochastic Convenience Yields, Interest Rates, and Jump Diffusions in the Spot, The Journal of Financial and Quantitative Analysis, Vol. 33, No. 1 (Mar., 1998), pp. 61-86